Mobile application for fruits freshness/ripeness detection - Cheah, Ui Shaun (2021)
Fruits play a crucial role in our diet as they contain nutrients that are vital for our health. These nutrients are important as they help us protect against chronic diseases. Fruits that are not fresh will not contain as many nutrients than when it was fresh. Thus, it is important to ensure that only fresh and ripe fruits are consumed. However, there exist a large number of consumers that do not know how to select fruits that are fresh when purchasing. Besides that, the fruit industry in Malaysia uses harmful chemicals in order to perform fruit inspections which makes the fruit to lose its nutrients. To solve the problems stated above, this paper proposes a mobile application that can detect freshness in fruits. To do this, this project utilizes Deep Learning technologies in conjunction with a mobile application in order to predict the freshness of fruits. Although there are several applications that can perform fruit freshness prediction, they require the user to have several external devices in order to accurately predict its freshness. Therefore, this project will focus on developing an application that can do fruits freshness prediction accurately without needing extra devices.